Analisis Penilaian Dan Harapan Pasien Poli Gigi Dan Mulut Dengan Metode Spider Web Berdasarkan Dimensi Mutu Dabholkar - Mustika Dyah Permatasari; Setya Haksama (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2015)
ABSTRACT There are many factors that determine health care service quality. One of them is the internal factor. This research was done to arrange recomendation increasingdental polyclinic utilization based on Dabholkar quality dimention.This was an observational study with cross sectional design of the 70 respondents who are representing dental polyclinic’s patient in a month. Data were collected by questionnaires distributed to respondents to identify the respondent’s assessment and expectation about physical aspects dimension, reliability dimension, personal interaction dimension, problem solving dimension, and policy dimension of dental polyclinic service quality. The conformity between assessment and expectation of respondentson service quality was analyzed based on Dabholkar quality dimension by using spider web. The results showed that most dimensions have been suitable about reliability dimension, personal interaction dimension and problem solving dimension. While the conformity of physical aspects dimension and policy dimension are not quite good. The conclusions showed that physical aspects dimension and policy dimension are the top priority, while reliability dimension, personal interaction dimension and problem solving dimensionneed repairement are still need to be maintained.  Keywords: Dabholkar quality dimension, physical aspects dimension, policy                     dimension